The Potential Application of Nanocarriers in Delivering Topical Antioxidants - Zulfan Zazuli; Rika Hartati; Cornelia Rosasepti Rowa; Sukmadjaja Asyarie; Satrialdi (Pharmaceuticals)
The imbalance in the production of reactive oxygen species (ROS) with endogenous antioxidant capacity leads to oxidative stress, which drives many disorders, especially in the skin. In such conditions, supplementing exogenous antioxidants may help the body prevent the negative effect of ROS. However, the skin, as the outermost barrier of the body, provides a perfect barricade, making the antioxidant delivery complicated. Several strategies have been developed to enhance the penetration of antioxidants through the skin, one of which is nanotechnology. This review focuses on utilizing several nanocarrier systems, including nanoemulsions, liposomes, solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), and polymeric nanoparticles, for transporting antioxidants into the skin. We also reveal ROS formation in the skin and the role of antioxidant therapy, as well as the natural sources of antioxidants. Furthermore, we discuss the clinical application of topical antioxidant therapy concomitantly with the current status of using nanotechnology to deliver topical antioxidants. This review will accelerate the advancement of topical antioxidant therapy.